(untitled) (Research, Society and Development, 2022)
The increase in longevity tends to considerably increase the percentage of the elderly population in the country, stimulating the development of studies that allow us to understand collaborative factors for healthy and active aging. The objective of this study is to evaluate the influence of a physical exercise program on the quality of life (QoL) of the elderly in an extension project at the Universidade do Estado de Minas Gerais, Unidade Divinópolis. This is a “before and after” longitudinal analytical study, in which data from a group of individuals were recorded using a specific and validated questionnaire for this purpose. The WHOQOL-OLD questionnaire was applied, which is structured in 24 closed questions, of the five-point Likert scale type and divided into six facets: Sensory Functioning (FS); Autonomy (AUT); Past, present and future activities (PPF); Social Participation (PSO); Death or Dying (MM); Intimacy (INT). The main results indicate that physical activities contribute to the maintenance of the elderly’s QoL; the type of exercise has no influence on the QOL perspective; socialization tends to contribute to QOL through the feeling of companionship and recognition; increasing age tends to keep the elderly away from the practice of exercises, generating idleness and loss of QoL. It is concluded that the regular practice of physical exercises developed collectively tends to present in the medium/long term favorable responses regarding the psychic, physical and social aspects of the elderly, and consequently in their QOL.